1991
DOI: 10.3758/bf03198491
|View full text |Cite
|
Sign up to set email alerts
|

The abstraction of form in semantic categories

Abstract: Undergraduates were asked to generate a name for a hypothetical new exemplar of a category. They produced names that had the same numbers of syllables, the same endings, and the same types of word stems as existing exemplars of that category. In addition, novel exemplars, each consisting of a nonsense syllable root and a prototypical ending, were accurately assigned to categories. The data demonstrate the abstraction and use of surface properties of words.What types of organization do people use when they lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 24 publications
(16 reference statements)
0
32
0
Order By: Relevance
“…Rubin, Stoltzfus, & Wall, 1991). We predicted that individuals primed with power would produce ideas less influenced by the presence of salient examples, which typically act as barriers to creativity, compared with baseline participants who had not been primed with power.…”
Section: Experiments 1: Creating Product Labelsmentioning
confidence: 99%
“…Rubin, Stoltzfus, & Wall, 1991). We predicted that individuals primed with power would produce ideas less influenced by the presence of salient examples, which typically act as barriers to creativity, compared with baseline participants who had not been primed with power.…”
Section: Experiments 1: Creating Product Labelsmentioning
confidence: 99%
“…Three categories (analgesics, elements, and pastas) were chosen from the set that was originally used by Rubin et al (1991). In the natural condition, six naturally occurring exemplars for each of the three categories were taken from that earlier study (e.g., spaghetti for pastas, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…Rubin, Stoltzfus, and Wall (1991) asked participants to generate novel names for new products (e.g., laundry detergents) and found that participants tended to conform to existing product names. More specifically, participants used the same number of syllables, the same word endings, and the same sort of word stems as those that were quite common for existing exemplars from each ofthe several categories tested (e.g., analgesics, pastas, etc.).…”
mentioning
confidence: 99%
“…How should one go about collecting empirical data on such hypothetical shared knowledge structures? A standard way to obtain a schema, independent of the recall of actual instances, is to have people generate imaginary instances of the schema of interest (Rubin & Kontis, 1983;Rubin, Stolzfus, & Wall, 1991;Rubin, Wallace, & Houston, 1993). We did so in Study 2, when we asked people to generate and date important events that are likely to occur in a prototypical life course.…”
Section: A Reanalysis Of Findings On Cultural Age Normsmentioning
confidence: 99%